PROCESS ANALYSIS OF BUSINESS INCUBATORS IN CREATING PRODUCT INNOVATION AT PT. TELKOM INDONESIA (PERSERO) TBK. (A CASE STUDY OF DIGITAL AMOEBA) - Ruhyana, Vivie Insani Saffanah Qalbi (Universitas Negeri Yogyakarta, 2023)
Abstract- Business incubators are developing in Indonesia, especially the incubator business under the company auspice. This incubator program functions as an innovation laboratory that aims to find new hidden talents within employees. Indeed, business incubators face various challenges such as human resources, capital, technical validation, regulation, and market potential as well as aligning products produced with the goals of the main company. This study aims to further identify the incubation process and evaluate the challenges that hinder startups to survive after passing the incubator process. The evaluation covered the pre-incubation stage, the core incubation stage, and the post-incubation stage. These components were analyzed to see the learning process in the incubator. This study used qualitative methods and data were collected through in-depth interviews. Besides, it used secondary data. The results of this study are expected to be a learning evaluation tool in the incubator and guidelines in incubation management in the future. Besides, this study is also expected to stimulate the incubator to continue developing.